Exploring the application domain of adaptive structures. (15th July 2018) - Senatore, Gennaro; Duffour, Philippe; Winslow, Pete
Highlights: Exploration of the application domain for adaptive planar reticular structures. Energy savings sensitivity to static indeterminacy is low. Energy savings sensitivity to load probability distribution is low. For slender structures, the adaptive solution is advantageous in monetary cost terms. An optimal region in terms of energy and monetary costs is identified. The optimal region is broadly that of stiffness-governed structures. The adaptive solution performs best for slender structures and low live to dead load ratios. For tall structures, the optimal region includes deep structures. Abstract: Using a previously developed design methodology it was shown that optimal material distribution in combination with strategic integration of the actuation system lead to significant whole-life energy savings when the design is governed by rare but strong loading events. The whole-life energy of the structure is made of an embodied part in the material and an operational part for structural adaptation. Instead of using more material to cope with the effect of loads, the actuation system redirects the internal load-path to homogenise the stresses and change the shape of the structure to keep deflections within limits. This paper presents a systematic exploration of the domain in which adaptive two-dimensional pin-jointed structures are beneficial in terms of whole-life energy and monetary costs savings. Two case studies are considered: a vertical cantilever truss representative of a multi-storey building supported by an exoskeleton structure and a simply supported truss beam which is part of a roof system. This exploration takes five directions studying the influence of: (1) the structural topology (2) the characteristics of the load probability distribution (3) the ratio of live load over dead load (4) the aspect ratio of the structure (e.g. height-to-depth) (5) the material energy intensity factor. Results from the main five strands are combined with those from the monetary cost analysis to identify an optimal region where adaptive structures are most effective in terms of both energy and monetary savings. It was found that the optimal region is broadly that of stiffness-governed structures. For the cantilever case, the optimal region covers most of the application domain and it is not very sensitive to either live-to-dead-load or height-to-depth ratios thus showing a wide range of applicability, including ordinary loading scenarios and relatively deep structures.